Pengaturan Hukum Mengenai Kedudukan Keputusan yang Dimohonkan kepada Pejabat Tata Usaha Negara - Yogi Pratama; Muhammad Irsyad Tirtasah; Yarni Nikita Ahmady; Ardoyo Wardhana (Faculty of Law Hang Tuah University, 2019)
This research aims to find out two matters. the first matter is to find out how the paradigm of Law Number 5 Year 1986 and Law Number 30 Year 2014 on decisions that are petitioned to State Administrative Officials (hereinafter TUN Officials). Second, to find out the legal implications of the differences in the position of decisions that are applied to TUN Officials based on Law Number 5 Year 1986 and Law Number 30 Year 2014. The following research results, (1) that related to the paradigm of Article 3 of the Law on State Administrative Court and Article 53 of the Government Administration Law, should be related to the type of decision.. (2) The legal implication of the decision’s differences that have been petitioned to TUN officials may allow confusion to occur when it is applied in the process of administering the government and also the process in court.